In vivo Proximity Labeling of Nuclear and Nucleolar Proteins by a Stably Expressed, DNA Damage-Responsive NONO-APEX2 Fusion Protein - Trifault, Barbara; Mamontova, Victoria; Burger, Kaspar (Frontiers in Molecular Biosciences, 2022)
Cellular stress can induce DNA lesions that threaten the stability of genes. The DNA damage response (DDR) recognises and repairs broken DNA to maintain genome stability. Intriguingly, components of nuclear paraspeckles like the non-POU domain-containing octamer RNA-binding protein NONO, participate in the repair of DNA double-strand breaks (DSBs). NONO is a multifunctional RNA-binding protein (RBP) that participates in the retention and editing of messenger (m)RNA as well as in pre-mRNA processing. However, the role of NONO in the DDR is poorly understood. Here, we establish a novel human U2OS cell line that stably expresses NONO fused to the engineered ascorbate peroxidase 2 (U2OS:NONO-APEX2-HA). We show that NONO-APEX2-HA accumulates in the nucleolus in response to DNA damage. Combining viability assays, subcellular localization studies, co-immunoprecipitation experiments, and in vivo proximity labeling, we demonstrate that NONO-APEX2-HA is a stably expressed fusion protein that mimics endogenous NONO in terms of expression, localization, and bona fide interactors. We propose that in vivo proximity labeling in U2OS:NONO-APEX2-HA cells is capable for the assessment of NONO interactomes by downstream assays. U2OS:NONO-APEX2-HA cells will likely be a valuable resource for the investigation of NONO interactome dynamics in response to DNA damage and other stimuli.